Learning is sitting: student and staff perspectives on sitting less at Maastricht University - Erkens, Roy H. J.; Chim, H. Q.; Poole, Nikita L.; Wasenitz, Stella; Savelberg, Hans H. C. M. (Frontiers in Education, 2025)
University students are often sedentary due to classroom designs that limit opportunities for movement. However, more activity can improve students’ mental-health and academic results. This study investigates the needs of students and teachers in terms of ‘less sitting’ at Maastricht University (the Netherlands). Furthermore, it explores whether standing desks are feasible and acceptable interventions for ‘less sitting’ in the context of Problem-Based Learning. Two focus groups of five students and eight interviews were used to investigate the needs of students and staff, and 108 students from three different study modules filled out a questionnaire to address the feasibility and acceptability of standing desks. Students and staff of six faculties and 11 study programmes were included in the research. We find that students and staff at Maastricht University expressed the need for more active education. They flag the lack of appropriate educational spaces at Maastricht University for more active education and the necessity for socio-cultural norms change as largest limitations. Students and staff are furthermore mainly neutral in terms of the acceptability and feasibility of implementing standing desks at Maastricht University in a Problem-Based Learning setting. They report the same opinions in terms of dynamics, learning, health, and frequency of activity in the classroom as in more traditional university programmes. However, the participants in this study state that more attention for posture is needed during standing tutorials. They also comment that module design should make standing desks a logical element of the class dynamics. Our findings at Maastricht University indicate that an ambition for a more active classroom should go hand in hand with proper classroom and educational designs to make the most out of it.